Current Status and Species Diversity of Seagrass in Panjang Island, Banten - Yayuk Sugianti; Mujiyanto Mujiyanto (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2020)
Damage to seagrass beds in Panjang Island, Banten, has increased every year. The most significant decline occurred at an interval of 2000-2005 with a decrease of about 22.9 ha. Seagrass damage continued to increase at the year between 1989-2002 as a result of natural stone mining and coastal reclamation activities to become industrial areas and ports. The objective of this study was to determine the characteristics of the species and current status of seagrass communities in Panjang Island waters, Banten. Analysis of seagrass data included identification of species, frequency, density, percent coverage, and important value index. Based on these results, it was found three species of seagrass on Panjang Island, Banten, including species of Enhalus acoroides, Cymodocea serrulata, and Syrongodium isoetifolium. The percentage of seagrass coverage at five different research stations, the highest percentage of seagrass coverage was at station IV with a percentage of coverage of 48.94% and the lowest coverage was obtained at station V of 10.28%. The calculation of the importance value index (INP) of seagrass in Panjang Island waters, Banten, showed that the highest INP value was found in the Cymodocea serrulata seagrass species which was 41.47 and the lowest was found in the Syrongodium isoetifolium seagrass species which was 16.81. PCA analysis was also conducted to determine the relationship of seagrass density with chemical physics parameters. The results obtained showed the condition of seagrass ecosystems in Panjang Island waters, Banten, which was at a level of moderate to severe damage. The results of PCA analysis showed that water temperature, nitrate concentration, DO, and TSS greatly influenced the density of seagrass in these waters.